Meaningful involvement of children and young people in health technology development. (18th August 2022) - Wheeler, Gemma; Mills, Nathaniel; Ankeny, Ursula; Howsley, Philippa; Bartlett, Clare; Elphick, Heather; Dimitri, Paul
Abstract: The anatomical, physiological, and developmental changes which arise as children mature through childhood and adolescence support the need to develop new health technologies that meet the specific requirements of children and young people (CYP). Failing to involve CYP during the development of technology increases the risk that the outcome falls short of their expectations and needs, leading to rejection of novel interventions. Through participation in health technology development, CYP and their families can provide context, insight, personal experience and tacit knowledge to ensure that the end-product is usable, acceptable, and can be integrated into its intended environment. A nuanced, balanced understanding of the methods that can be used to facilitate participation will support researchers in choosing an effective approach to involving CYP in health technology development. Methodological approaches include patient and public involvement and engagement, co-design, and experienced based co-design. These methods can be used in isolation or in combination, to facilitate meaningful involvement of CYP and encourage the development of impactful solutions, in consideration of the context, stakeholders, and objectives of the project. We provide the rationale and justification for involving CYP in health technology design and development, an explanation of the methods supporting meaningful involvement, and case studies exemplifying real world application of these methods with positive outputs.